Proses Pembelajaran Pada Masa Pandemi Covid-19 di SDN 03 Batursari Pemalang - Khoiruzzadi, Muhammad; Purnomo, Budi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to describe the learning process during the Covid-19 pandemic and the obstacles faced by teachers at SDN 03 Batursari Pemalang. This research is a field research using a qualitative approach. The subjects of this study were principals, teachers, students, and guardians of students at SDN 03 Batursari Pemalang. The results showed that learning during the Covid-19 pandemic used a combination of online and offline learning. Online learning by utilizing the WhatsApp group application as directed communication and to give assignments to students. In addition, the teacher also uses the youtube platform to explain the material and the google form is used to do assignments in the form of quizzes or description questions. Offline learning, commonly referred to as study groups, where learning is carried out face-to-face is limited while still paying attention to health protocols and an estimated maximum time of one hour of learning.